Training and Educational Program on Natural Dye Shibori Technique: Enhancing Community Skills and Eco-Creativity in Semarang: Indonesia - Widowati, Widowati; Sholikhah, Roudlotus; Atika, Atika; Nurmasitah, Sita; Wahyuningsih, Sri Endah (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
This community service activity focuses on environmental education and developing the community's creative skills through sustainable textile craft practices. The activity partners are the Kalisegoro community, Semarang, who have the potential to develop craft skills but are still limited in mastering environmentally friendly dyeing techniques and textile product innovation. The objective of this activity is to improve shibori technique skills based on natural dyes while fostering eco-creativity and environmental awareness in the community. This program was implemented for four weeks with the involvement of 25 participants. The activity stages include training and education on natural dyes, shibori printing techniques, direct practice of making shibori cloth using ketapang leaves (Terminalia catappa), as well as activity evaluation through pre- and post-training tests, observations, and interviews. The results of the activity showed a significant increase in participants' skills in making shibori with natural dyes, especially in aspects of technical competence, environmental understanding, and creative expression. The participant evaluation score increased from an average of 56.4% in the pre-training to 87.2% in the post-training. In addition to enhancing skills, this activity also has a social impact in the form of growing community collaboration, empowering women, and increasing awareness and support for sustainable fashion practices. This community service activity demonstrates that contextual, practical, and eco-creativity-oriented training is effective in increasing community capacity and contributing to the development of the creative economy and sustainable development at the local level.